The Effect of Periodontal Treatment on Circulating Tumor Necrosis Factor-Alpha and Insulin Resistance in Patients with Type 2 Diabetes Mellitus - Ola H. Ezzat; Suzan S. Ibrahim; Hala K. Abdel Gaber (Journal of King Abdulaziz University: Medical Sciences, 2023)
The aim of this study is to investigate the effect of periodontal treatment on the relation between inflammation and insulin resistance in patients with type 2 diabetes mellitus. Group I included 15 type -2 diabetic patients with chronic periodontitis; Group II were systemically healthy 15 patients with chronic periodontitis and family history of Type 2 diabetes mellitus; while Group III included 10 Type 2 diabetic patients without chronic periodontitis and was considered as a control group. Circulating TNF-? level, glycated hemoglobin, fasting blood glucose, fasting human serum insulin concentration as well as insulin sensitivity assessed using HOMA-IR were measured before and after 3 months of periodontal treatment that were composed of conventional mechanical treatment with adjunctive systemic doxycycline therapy. Higher levels of the assessed parameters were observed in type 2 diabetic patients with periodontitis compared to those without periodontitis. Circulating TNF-? level significantly was reduced after periodontal treatment. The results indicate that periodontal treatment was effective in improvement of insulin sensitivity and glycemic control in Type 2 diabetics, which could be explained by reduced serum TNF-? with its insulin resistance mediated effect.